Anger, social support, and suicide risk in U.S. military veterans. (February 2019) - Wilks, Chelsey R.; Morland, Leslie A.; Dillon, Kirsten H.; Mackintosh, Margaret-Anne; Blakey, Shannon M.; Wagner, H. Ryan; Elbogen, Eric B.; ,
Abstract: There have been considerable efforts to understand, predict, and reduce suicide among U.S. military veterans. Studies have shown that posttraumatic stress disorder (PTSD), major depression (MDD), and traumatic brain injury (TBI) increase risk of suicidal behavior in veterans. Limited research has examined anger and social support as factors linked to suicidal ideation, which if demonstrated could lead to new, effective strategies for suicide risk assessment and prevention. Iraq/Afghanistan era veterans ( N  = 2467) were evaluated in the ongoing Veterans Affairs Mid-Atlantic Mental Illness Research, Education and Clinical Center (MIRECC) multi-site Study of Post-Deployment Mental Health on demographic and psychological variables. Analyses revealed that suicidal ideation in veterans was positively associated with anger and negatively associated with social support. These results remained significant in multivariate logistic regression models controlling for relevant variables including PTSD, MDD, and TBI. Examining interrelationships among these variables, the analyses revealed that the association between PTSD and suicidal ideation was no longer statistically significant once anger was entered in the regression models. Further, it was found that TBI was associated with suicidal ideation in veterans with MDD but not in veterans without MDD. These findings provide preliminary evidence that suicide risk assessment in military veterans should include clinical consideration of the roles of anger and social support in addition to PTSD, MDD, and TBI. Further, the results suggest that suicide prevention may benefit from anger management interventions as well as interventions aimed at bolstering social and family support as treatment adjuncts to lower suicide risk in veterans.